HUMAN EXISTENCE AND MEANING OF LIFE: ALTERNATIVE PHILOSOPHICAL SOLUTIONS TO MULTIDIMENSIONAL EDUCATIONAL PROBLEMS - Arizona, Kurniawan; Sarjan, M; Rokhmat, Joni; Sucilestari, Ramdhani; A, Syahrial; Mertha, I Gde; Syamsuddin; Syahidi, Khaerus (Jurnal Tatsqif, 2022)
Humans are an important element in discussing all kinds of aspects and problems. Because humans occupy these positions (conceptors and administrators). In the world of human education as the main actor or actor. All aspects and tasks are carried out by humans. The meaning of life is important to be reviewed in the world of education. So the purpose of writing this paper is to understand and describe human existence and the meaning of life as an alternative philosophical solution to the problems of multidimensional education. This research includes library research, namely research that focuses on the discussion of the literature in the form of books, journals, papers, and other writings related to the object of research. Understanding human existence in education by understanding the position of humans in various educational factors (humans as educators, humans as students and education managers) should be an afterthought. If you look specifically at the existence of humans as educators, a common thread can be drawn that an educator must be able to be a role model (teacher-to be nurtured and imitated) for students and able to protect the situation of the teaching and learning process in order to pour and teach science to humans called learners. On the other hand, humans as students are also required to fulfill a code of ethics in studying. The world of education, apart from being an institution that develops intellectual abilities, also strives for the formation of character qualities that can be seen from the mindset and attitude patterns, students' perceptions of their life experiences, and faith in God which in turn will also affect the meaning of students' lives. Meaning is the most basic thing that distinguishes humans from animals.